Do Normative Issues Outperform Deterrence for Compliance With Drug Laws? - Quintas, Jorge (International criminal justice review, 2024)
This article tests the impact of deterrence and normative variables in the estimation of drug use among both detected drug users and university students. Consistent with perceptual deterrence research, we expect: (a) a stronger effect of normative variables on estimation of drug use compared to deterrence variables and (b) that any deterrent effect would be restricted to detected drug users. In Portugal, we conducted a cross-sectional survey with detected drug users (N = 147) and with a sample of university students (N = 247). The main results show that normative variables outperform deterrent variables as predictors of intention to use drugs. Descriptive norms have a greater influence on the estimation of drug use in both groups, and proximal social norms have robust effects among university students. Core elements of the deterrence model are not related to the intention to use drugs. Personal certainty of being caught has even an unexpected positive correlation with this intention. A small deterrent effect is limited to the general certainty variable and only among more law-abiding people. The overall findings are consistent with a normative perspective on law compliance and highlight the importance of including all different normative and deterrent variables in models estimating drug use.